Influência da fermentação sobre as propriedades físico-químicas e sensoriais de café conilon (Coffea canephora Pierre ex. Froehner variedade Vitória) - Prudêncio, Estefânia Pecegueiro (2017)
Coffee is a commodity of economic importance, which the quality of green coffee beans is relevant in the commercialization. The harvesting and processing forms impact cupping quality. Coffee can be prepared by the dry, semi-dry and wet processes. In wet processing, besides the natural fermentation, enzymes or inocula can be added to carry out the degumming. However, the influences of the fermentation induced need to be verified in the characteristics of the grain. Thus, this work was carried out with the objective of evaluating the influence of the induced fermentation on the physicochemical and sensorial properties of conilon coffee. Fruits of conilon coffee (Coffea canephora Pierre ex. Froehner), variety Vitória, were manual strip harvested and the ripe cherries were selected. The experiment was carried out in two phases. In the first phase, using a factorial design, samples of coffee fruits were sanitized, peeled and inoculated with three inocula: Saccharomyces cerevisiae, Saccharomyces bayanus, and Brettanomyces bruxellensis trois, at concentrations of 0,00, 0,05, 0,10, 0,15 and 0,20% m m-1 . In the second phase, six preparing forms were compared: dry, semi-dry, wet, semi-solid, dry realized by farmer, and wet with addition of Saccharomyces cerevisiae, Saccharomyces bayanus, and Brettanomyces bruxellensis trois, at concentration of 0,20% m m-1 . The physicochemical properties evaluated in both phases were moisture, pH, total titratable acidity, antioxidant activity, total phenolic compounds, color, total and reducing sugars, electrical conductivity and potassium leaching. Samples obtained from the first and second phases were classified according to type, sieve and cupping. For the first phase of the experiment, there were no significant differences among the treatments for the physicochemical properties of moisture, pH, total titratable acidity, antioxidant activity, total phenolic compounds, total and reducing sugars, electrical conductivity and potassium leaching. However, there was a significant color difference in the coordinates L*, a* and b*. Classifications by type, sieve and cupping did not differ among studied treatments. For the second phase, the physicochemical properties of moisture, pH, total titratable acidity, antioxidant activity, total phenolic compounds, total and reducing sugars, electrical conductivity and potassium leaching did not differ statistically. However, color analysis and sorting by type, sieve and sensory differed. The coffee cupping showed that the wet processing using inoculant provided distinctive taste and aroma.